Research on Application and Development of Competitive Sports Simulation Based on Virtual Reality Technology - Chuan, J. L. (Advanced Materials Research, 2011)
With the popularity of the concept of the "Hi-tech Olympics" and the rapid development of the computer technology, the modern science and technology, characteristic of "digital technology", have permeated into all areas of sports. In particular, the virtual reality technology plays an important role in the competitive sports training. The paper discusses the major functions of the virtual reality technology and its mutual relations with the sports system simulation, explores the application scope of the technology in the sports system simulation field, and makes an overall analysis of its application prospects and trend in the sports training simulation in hope of pushing forward the research on "digital technology" in the competitive sports simulation and the relevant fields.